Assessment of slope stability - Harabinova Slavka; Panulinova Eva (MATEC Web of Conferences, 2017)
The paper deals with the assessment of slope stability on the road II/595 near the village Zlatno before and after the landslide caused by floods in 2010. The calculation of factor of safety was made using GEO 5 software. For proposal comprehensive assessment and possible remedial work is necessary to know the geological conditions and choose the appropriate method for assessing slope stability. The critical factors of safety have been determined by Petterson, Bishop and Sarma Methods. After finding the most unfavorable slip surface a proposal of remediation measures has been made. The paper presents various solutions to ensure slope stability of the road. The most appropriate remedial action is Variant III - reinforced slope due to its greater factor of safety.